THE RELATIONSHIP BETWEEN RELIGIOSITY WITH AGGRESSIVE BEHAVIOR IN ELEMENTARY SCHOOL STUDENTS - Wibowo, Cruyzera Harda Rifya; Nastiti, Dwi (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study aims to determine the extent of the relationship between religiosity and aggression behavior of elementary school students. The population in this study were students of SDN Tanggul Wonoayu in Sidoarjo from all active students in grades 4, 5, 6 totaling 115 students. Method: The sampling technique used saturated sampling technique. This study uses correlational quantitative research methods. In the data collection method using the scale model method, namely the Likert scale. The scale used in the study was the aggressive behavior scale and the religiosity scale. The analysis used is the spearman’s correlation test using the SPSS 29.0.0.0 for Windows application. Results: The results of data analysis obtained r -0,395 with a significance level of p < 0,001 < 0,05. So the hypothesis is accepted so that there is a negative relationship between religiosity and aggression behavior. Novelty: Previous research found differences in research regarding religiosity with aggression behavior in students. This researcher offers a review by analyzing the relationship between religiosity and aggression behavior in elementary school students.